Low-frequency radio observations of the galaxy cluster CIZA J2242.8+5301 - Weeren, RJ van; Intema, Huib; Rottgering, H.J.A.; Bruggen, M.; Hoeft, M.
Some disturbed galaxy clusters host diffuse elongated radio sources, also called radio relics. It is proposed that these relics trace shock waves in the intracluster medium (ICM). Within the shock waves, generated by cluster merger events, particles are accelerated to relativistic energies, and in the presence of a magnetic field synchrotron radiation will be emitted. CIZA J2242.8+5301 is a disturbed galaxy cluster hosting complex diffuse radio emission, including a so-called double radio relic. Here we present new Giant Metrewave Radio Telescope (GMRT) radio observations of CIZA J2242.8+5301 at 325 and 150 MHz. We detect the double radio relic at 150 and 325 MHz. The very deep 150 MHz image reveals the presence of large-scale diffuse emission between the two radio relics.